Reputation system for an e-commerce system using fuzzy logic - Zeon Poee, Liang (2012)
E-commerce system is one of the most rapid-growing systems online. E-commerce system is the medium for buying and selling goods on the internet.However,on internet all the online users cannot recognize each other the way they do in real life.In E-commerce system where transaction is made and money is involved,the reliability of a seller holds a substantial amount of importance.Hence,there are many trust and reputation systems are introduced for e-commerce system. However,many of the existing systems are based on the simple calculation which is vulnerable to user manipulations. This may increase the chances of dishonest rating and reduce the reliability of the reputation system. This project aims to overcome this problem by applying fuzzy logic in the reputation system.By using fuzzy logic to compute a weight based on the user‘s information, each rating is multiplied with different weight.This can increase the difficulty of manipulation by dishonest users and increase the reliability of the system.The result of applying fuzzy logic shows that it can indeed prevent certain scenarios of dishonest manipulation in user rating.